Clopidogrel Hypersensitivity: Pathogenesis, Presentation and Diagnosis - Ford, Megan K.; Cohn, John R. (Current Vascular Pharmacology, 2019)
This paper provides an overview of the pathogenesis, presentation and diagnosis of clopidogrel hypersensitivity. The majority of clopidogrel hypersensitivity cases are due to a T cell mediated Gell and Coombs Type IV reaction. History, histology, and patch testing have shown consistency with a T cell mediated mechanism. Clopidogrel reactions most commonly present as a mild delayed maculopapular erythematous rash 5 to 10 days after introduction of the drug, and do not always require discontinuation of the drug. Severe cutaneous, systemic, and immediate adverse reactions to clopidogrel are rare. For the diagnosis of clopidogrel hypersensitivity, drug causality can be determined using patch testing, or for mild reactions, recurrence of symptoms after drug reintroduction, although neither are required for diagnosis.
Keywords: diagnosis